GAS RESERVOIR ENGINEERING - JOHN LEE, ROBERT A. WATTENBARGER (Estados Unidos SPE, 1996)
NATURAL GAS PRODUCTION HAS BECOME INCREASINGLY IMPORTANT IN THE US AND THE WELLHEAD REVENUE GENERATED FROM IT IS NOW GREATER THAN THE WELLHEAD REVENUE GENERATED FROM OIL PRODUCTION. BECAUSE THIS TREND EVENTUALLY WILL BE FOLLOWED WORLDWIDE, WE FEEL THAT IT
Keywords: DEPOSITOS DE ALMACENAMIENTO; GAS NATURAL; SIMULACION DE YACIMIENTOS